2014
DOI: 10.3892/mmr.2014.2467
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression profiling of matrix metalloproteinases and tissue inhibitors of metalloproteinases in females with or without pelvic organ prolapse

Abstract: Abstract. Pelvic organ prolapse (POP) is a common disorder that can disturb the health and quality of life of females. However, the basic pathophysiology and underlying mechanism of POP are not fully understood. Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) have been reported to be associated with the onset and development of POP. In the present study, to characterize the differential expression profile of MMPs and TIMPs in female patients with and without POP, a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…After assessing the full texts of nine potentially relevant articles, we determined five eligible case–control studies. Of the four excluded studies, one was irrelevant to MMP‐1 expression, one was excluded because it was a repeatedly published literature source, and two investigations were excluded because the numbers or percentages of cases and controls in the different staining groups were not reported . Although two of the studies were by the same first author and conducted in the same country, the included participants were different.…”
Section: Resultsmentioning
confidence: 99%
“…After assessing the full texts of nine potentially relevant articles, we determined five eligible case–control studies. Of the four excluded studies, one was irrelevant to MMP‐1 expression, one was excluded because it was a repeatedly published literature source, and two investigations were excluded because the numbers or percentages of cases and controls in the different staining groups were not reported . Although two of the studies were by the same first author and conducted in the same country, the included participants were different.…”
Section: Resultsmentioning
confidence: 99%
“…15 Nevertheless, some studies compared the MMP9 activity in the vaginal tissues of women with and without a genital prolapse and found an increase in MMP9 activity in association with this disease. 20,22 In our review, 1 study that aimed to establish a relationship between the rs17576 and rs3918242 MMP9 polymorphisms and the risk of POP was performed by Chen et al, 23 which included 92 Chinese women with POP and 152 women without the disease. The authors observed, after a binary logistic regression, that the MMP9 rs17576 polymorphism seemed to be associated with POP, but did not find any association between the MMP9 rs3918242 polymorphism and the risk of POP, which is in line with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…2 In addition, POP is the main reason for surgery in aging women. 3 The etiology of POP is considered multifactorial, and several risk factors, such as advanced age, pregnancy, obesity, neuropathies, ethnicity, hysterectomy, instrumental delivery, and menopause, have been identified. Recent evidence suggests the existence of a genetic component with a 3.2-to 2.4-fold increased risk for the mothers and sisters of affected women, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of POP in patients with type I and III collagen disorders, such as Ehlers-Danlos and Marfan syndromes, corroborates the importance of studying the genetic background of patients with the disease. 3,4 Older age and parity are the most significant etiological factors, but they do not fully explain the origin and progression of pelvic floor dysfunction in all women, since POP has been observed in nulliparous women and has been absent in many multiparous women. 5 The main mechanism of pelvic floor dysfunction is the weakening of the structures that support the pelvic organs: connective tissue in the form of ligaments and endopelvic fascia, and the levator ani muscles.…”
Section: Introductionmentioning
confidence: 99%